Study of thermal stability and determination of effective activation energy values during degradation of unsaturated polyester copolymers in the air atmosphere - Sarsenbekova, A.Zh.; Bolatbay, A.N.; Morgun, V.V.; Havlicek, D.; Davrenbekov, S.Zh.; Nasikhatuly, E. (KU Publ., 2022)
The study of the kinetic parameters of copolymers based on polyethylene glycol fumarates, as well as the external and internal effects on them, is essential for production processes at various levels. This will solve a whole range of issues in the field of the shelf life of materials and storage conditions. All these point to the relevance of this research. The authors of the research attempt to test the most common thermogravimetric data processing methods and to improve them in terms of the quality of the predictive capabilities of the resulting regression equation. Both of them are important for the production of initial components and the manufacture of the final product from the studied materials. Therefore, the study and further use of the numerical data of the TG/DTA curves applies to both theoretical and practical branches of science. Thus, summarizing the experimental data on the thermal stability studies, we assume that p-EGF: AA copolymers with compositions of 21.03:78.97 and 68.96:31.04 wt.% have a relatively high degree of resistance to heating. It was found that the calculation by the FR method agreed well with the results of the KAS method. It should be noted that for the p-EGF: AA copolymer (21.03:78.97 wt.%) at heating rates of 5.0, 10.0, 20.0 °С∙min–1, the average activation energy data obtained for two methods increase in the following series: KAS E = 187.34 kJ /mol <FR E = 200.17 kJ/mol.
Ауа атмосферасындағы қанықпаған полиэфир сополимерлерінің деградациясы кезінде жылу тұрақтылығын зерттеу және активтендіру энергиясының тиімді мәндерін анықтау
Изучение термической стабильности и определение эффективных значений энергии активации при деградации сополимеров ненасыщенных полиэфиров в атмосфере воздуха
Keywords: thermogravimetry; thermal analysis; kinetic parameters; copolymers; polyethylene glycol fumarate; acrylic acid; activation energy; polyesters